DEVELOPMENT OF ANIMATION VIDEO LEARNING MEDIA FOR URBAN DRAINAGE COURSES IN BUILDING ENGINEERING EDUCATION - Muhamad Arin Fatkhul Huda; Arris Maulana (LPPM Universitas Negeri Jakarta, 2022)
This study aims to obtain a video-based learning media animation development on Urban Drainage course using Adobe After Effect in Education of Building Engineering, Faculty of Engineering, State University of Jakarta. The research implementation time is April to August 2020. The development model used in this study is 4D model by Thiagarajan, which consist of define phase, design phase, development phase, and disseminate phase. The instrument used in this research was a questionnaire for need analysis, product feasibility test by experts, and product users. The result of research and product development is an animation video consisting of 4 video materials used for one semester. The results of validation by material expert get an average percentage 80% and included in feasible category. The results of validation by media expert get an average percentage 92,5% and included in very feasible category. The product assessment results by students as product users get a percentage 88,9% and included in the excellent category.